EKSPEKTASI KLIEN DALAM KEBIJAKAN AUDIT - KARTIKA SARI, ADE (: 2303-1719)
KAP demanded to be able to act independent on audit judgment to the clien. KAP faces trouble to act independent due to some circumstances accured which cause clients to have hope to be able to Influence the audit judgment with was done by the KAP. Long term relationship between the clients and KAP causes the clients and KAp causes the clients have some expectations to be able to influence the audit judgment long-term relationship caused emotional bundling between the clients and KAP, as the client have courage to push the KAP, so the audit judgment which was done could give advantages to the clients. The importance of the clients for KAP also causing clients to have some expectations to able to influence the audit judgment done by the KAP. Economy contributions given by clients to KAP causing clients to have huge confidence of having ability to influence the audit judgment. One way to press clients strong expectation on KAP audit judgment by KAP rotating by auditors hired by clients with the rotate policy, the relationship between KAP and auditors which are too close could be pressed, to the possibility of the clients having big expextation to the audit judgment is becoming lower.